Sensitization to oxaliplatin in HCT116 and HT29 cell lines by metformin and ribavirin and differences in response to mitochondrial glutaminase inhibition - Richard, Silvina Mariel (2015)
Aim of study: In the present study, we evaluated the effect of ribavirin and metformin on the sensitivity of oxaliplatin and 5‑fluorouracil (5‑FU) on colon cancer. Materials and Methods: Cell viability of two commercially available colon cancer cell lines (HT29 and HCT116) were analyzed by sulforhodamine B (SRB) assay. Results: A clinically achievable and nontoxic concentration of ribavirin and metformin showed a significant synergistic effect on oxaliplatin in HT29 and HCT116 cell lines. Ribavirin showed a synergistic effect on oxaliplatin in HT29 (R = 2.93, P < 0.001) and HCT116 (R = 1.71, P < 0.001), while only in HT29 metformin synergized with oxaliplatin by 2.66 (± 0.28, P < 0.01). In addition, both cell lines showed significant differences in response to Compound 968, inhibitor of mitochondrial glutaminase activity. Conclusion: The data suggested that these cell lines not only turn to metabolic different sustainability process after oxaliplatin treatment but that they also have different basal metabolic requirements of glutamine in vitro which can be exploits in the future for colorectal cancer (CRC) treatment and further studies are required.